so sánh : ( 3 + 1). (3^2 + 1). ( 3^4 + 1). ( 3^8 + 1) và 3^16 – 1 26/07/2021 Bởi Eden so sánh : ( 3 + 1). (3^2 + 1). ( 3^4 + 1). ( 3^8 + 1) và 3^16 – 1
Đáp án: \[\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right) < {3^{16}} – 1\] Giải thích các bước giải: Ta có: \(\begin{array}{l}A = \left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\ \Rightarrow 2A = 2.\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\ \Leftrightarrow 2A = \left( {3 – 1} \right).\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\ \Leftrightarrow 2A = \left( {{3^2} – 1} \right).\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\ \Leftrightarrow 2A = \left( {{3^4} – 1} \right)\left( {{3^4} + 1} \right)\left( {{3^8} + 1} \right)\\ \Leftrightarrow 2A = \left( {{3^8} – 1} \right)\left( {{3^8} + 1} \right)\\ \Leftrightarrow 2A = {3^{16}} – 1\\ \Rightarrow A = \frac{{{3^{16}} – 1}}{2} < {3^{16}} – 1\\ \Rightarrow \left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right) < {3^{16}} – 1\end{array}\) Bình luận
Gửi bn
Đáp án:
\[\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right) < {3^{16}} – 1\]
Giải thích các bước giải:
Ta có:
\(\begin{array}{l}
A = \left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\
\Rightarrow 2A = 2.\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\
\Leftrightarrow 2A = \left( {3 – 1} \right).\left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\
\Leftrightarrow 2A = \left( {{3^2} – 1} \right).\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right)\\
\Leftrightarrow 2A = \left( {{3^4} – 1} \right)\left( {{3^4} + 1} \right)\left( {{3^8} + 1} \right)\\
\Leftrightarrow 2A = \left( {{3^8} – 1} \right)\left( {{3^8} + 1} \right)\\
\Leftrightarrow 2A = {3^{16}} – 1\\
\Rightarrow A = \frac{{{3^{16}} – 1}}{2} < {3^{16}} – 1\\
\Rightarrow \left( {3 + 1} \right)\left( {{3^2} + 1} \right)\left( {{3^4} + 1} \right).\left( {{3^8} + 1} \right) < {3^{16}} – 1
\end{array}\)